Assessment of isocenter alignment during CT colonography: Implications for clinical practice. Issue 4 (November 2018) - Olden, K.L.; Kavanagh, R.G.; James, K.; Twomey, M.; Moloney, F.; Moore, N.; Carey, K.; Murphy, K.P.; Grey, T.M.; Nicholson, P.; Chopra, R.; Maher, M.M.; et al.
Abstract: Introduction: Optimization of image quality and patient radiation dose is achieved in part by positioning the patient at the isocenter of the CT gantry. The aim of this study was to establish whether there was increased isocenter misalignment (IM) in CT colonography (CTC) scans by comparing patient position during the prone part of a CTC to patient position during renal stone protocol CT (CT-KUB) and patient position during the supine part of a CTC to patient position during abdominopelvic CT (CT-AP). Methods: Two hundred and twenty two consecutive outpatient adult CTC studies performed between January and December 2016 were retrospectively analyzed. Automated dose-tracking software was used to quantify IM in the x and y planes. Renal stone CT-KUB (n = 100) and standard CT-AP (n = 100) were used as comparison studies. Results: IM during CTC was significantly greater in the y-axis compared with the x-axis for both prone (p = 0.002) and supine (p < 0.001) scanning. IM was significantly greater during prone CTC compared with CT-KUB (p = 0.008) and during supine CTC compared with CT-AP (p = 0.0001). IM was shown to be slightly greater in studies performed by more experienced radiographers (p = 0.04). IM was not associated with patient age, gender or size (p > 0.05 for all). Conclusion: Isocenter misalignment is greater during CT colonography compared with CT-KUB or CT-AP. Strategies for improving patient positioning could include radiographer education and automated patient centering solutions. Highlights: Isocenter misalignment during CT results in decreased image quality and increased radiation dose. Isocenter misalignment is greater during CTC compared with CT-KUB or CT-AP. Isocenter misalignment was marginally increased in studies performed by more experienced radiographers. Ongoing radiographer education and audit may improve patient positioning.